Generic versus reference listed ropivacaine for peripheral nerve blockade: A randomised, triple-blinded, crossover, equivalence study in volunteers. (August 2021) - Opfermann, Philipp; Marhofer, Peter; Hopkins, Philip M.; Columb, Malachy O.; Zadrazil, Markus; Stimpfl, Thomas; Marhofer, Melanie; Zeitlinger, Markus
Abstract : BACKGROUND: Generic drug preparations do not require the same degree of scrutiny as the originally licensed preparation before they can be approved for clinical use. The permitted tolerance limits for bioequivalent preparations might be associated with clinically relevant differences for drugs with a narrow therapeutic index, such as local anaesthetics. OBJECTIVE: We compared pharmacokinetic and pharmacodynamic characteristics of generic and reference listed or original preparations of ropivacaine. DESIGN: The current healthy volunteer study used a randomised, triple-blinded, cross-over equivalence design. SETTING: Tertiary university hospital, Medical University of Vienna. SUBJECTS: Healthy male volunteers ( N =18) aged 18 to 60 years. INTERVENTIONS: A series of three ultrasound-guided ulnar nerve blocks separated by at least 6 days were carried out on each volunteer. Reference listed ropivacaine (Naropin TM ) was used for two blocks and a generic preparation of ropivacaine was used for the other block. Sensory block onset and duration were evaluated using loss of pinprick sensation. MAIN OUTCOME MEASURES: Duration of sensory block was the primary outcome. Secondary outcomes included time-to-onset of sensory block, ropivacaine pharmacokinetics from venous blood samples and pH of the preparations. Equivalence was evaluated using the ratios of means and 90% confidence intervals (CIs) of log transformed data. RESULTS: Equivalence was demonstrated for the primary outcome measure, the duration of sensory block [original : generic ratio 1.01 (90% CI 0.87 to 1.16); P  < 0.007] and all pharmacokinetic variables. Equivalence could not be concluded for time-to-onset of sensory block [reference : generic ratio 0.80 (90% CI 0.63 to 1.03); P  = 0.27], although reproducibility of this variable using our experimental model was lower than for other variables. The generic preparation was significantly more alkaline [difference 0.06 pH units (95% CI 0.04 to 0.07); P  < 0.0001]. CONCLUSION: Our finding of equivalence for sensory block duration and key pharmacokinetic variables between a generic and original preparation of ropivacaine is reassuring. The significant, but small, difference in pH is not clinically important. TRIAL REGISTRATION: EudraCT 2019-003148-61, German Clinical Trials Register (DRKS 00017750).